A Review on Positive Effects of Fenugreek as Feed Additive in Poultry Production - Adil , S.; Qureshi, Saim; Pattoo, R.A. (International Journal of Poultry Science, 2015)
Following the prohibition on usage of antibiotics as growth promoters, the researchers used other alternatives. Nowadays, phytogenic feed additives like herbs are in vogue and are incorporated in the diet in order to enhance productivity by improvement of digestibility, nutrient absorption and elimination of pathogens residents in the gut. Among the various phytogenics available, this review will focus on one such herb known as Fenugreek (Trigonella foenum graecum), locally known as Methi. It is mainly cultivated in India, Pakistan and China. It is rich in protein, fat, total carbohydrates and minerals such as calcium, phosphorus, iron, zinc, magnesium, fatty acids predominantly linoleic, linolenic, oleic and palmitic. Fenugreek seeds are the most important and useful part of fenugreek plant having many therapeutic effects like hypoglycaemic, antibacterial, ant-inflammatory, antipyretic, antimicrobial and antioxidant properties. They have a role in improving the performance of poultry birds by their antibacterial activity and positive effect on gut morphology. Besides, they help in decreasing the blood cholesterol levels in poultry, hence have a potential role in prevention of arteriosclerosis.